IODINE STATUS IN ASSOCIATION WITH DIETARY INTAKE AMONG SCHOOL GOING CHILDREN (6-12 YEARS) OF DIFFERENT ETHNICITY (Journal of Medical & Health Sciences Review, 2025)
Iodine deficiency is a major public health issue in underdeveloped nations, including Pakistan. A cross sectional research was conducted in Buner district of Khyber Pukhtunkhwa (KPK) to measure the status of iodine of school going children in three diverse ethnic groups. 150 children between the ages of 6 and 12 were preferred randomly for this study. Comprising 50 children from each ethnic group i.e., Sikh, Hindu and Muslims with the inclusion criteria that they should be free from any chronic disease and not using any iodine supplements. Data on socio demographic, anthropometric and dietary intake was recorded from the children on the pre-designed questionnaire. The iodine status was determined by measuring urinary iodine excretion (UIE). Salt iodine content was measured by using rapid test kit. Palpation method was used for goiter status assessment. Study results showed that UIE of Hindu children was significantly (p0.05) different in all three groups. The iodine content in salt and dietary iodine was significantly (p < 0.05) correlated with Urinary iodine excretion of Muslim group and was non-significantly (p>0.05) positively correlated with Sikh and Hindu groups. This study concluded that ethnicity is also an associated factor in iodine level of the people through influencing the dietary intake of iodine rich food, iodize salt consumption. Therefore, should be considered in the planning for eradication of iodine insufficiency disorders.